Tafa'ul's Provision in Adat with Society on the Subject of Islamic Law - Siahaan, Arifin; Prasetiya, Nurul Huda; Harahap, Arifuddin Muda (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Tafâ'ul is a good sentence that someone hears as a good sign. Tafâ'ul is used for things that are encouraging through an attitude of kindness towards Allah. Decorative Bathing is a bathing and sprinkling ceremony carried out after the marriage ceremony. The decorative bathing procession is usually carried out by the Batubara Malay community. When showering, the bride and groom wear clothes covered with private parts, then they are doused by sprinkling water by the practitioners of the decorative bath and their respective parents and the bride and groom are sprayed with water, then they untie the coconut leaves and close by washing the feet of each bride and groom. However, in the practice of ornamental bathing in Batubara Regency, there are still questions about the purpose and law of performing tafaul in the ornamental bathing tradition. This research is a type of field research, using a sociological juridical approach because this research has a close relationship with the subject and object of study. The data sources for this research consist of primary data sources which are data sources obtained directly from the community and secondary data sources, namely data sources that are not directly obtained from original sources such as books, journals, theses, and so on. The data collection method uses informant techniques, data obtained uses observation, interview and documentation techniques. From the results of this research, it is concluded that if the decorative bathing tradition is viewed using the istinbath method of Islamic law, namely with 'urf, it is included in 'urf sahih because it has a positive value, namely, to ask for goodness and blessings from Allah SWT so that the bride and groom will last forever, have good fortune, be healthy and many descendants.